EFEKTIFITAS ANTENATAL RISK QUESTIONNAIRE (ANRQ) DALAM DETEKSI DINI FAKTOR RESIKO GANGGUAN PSIKOLOGIS IBU HAMIL: Effectiveness Of Antenatal Risk Questionnaire (Anrq) In Early Detection Of Risk Factors Of Psychological Disorders For Pregnant Mothers - Dewi Pitriawati; Ririn Probowati; Niken Kinesti (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2022)
Psychological disorders in pregnant women are very at risk of causing various health problems in both the mother and fetus. The implementation of early detection of risk factors for psychological disorders of pregnant women should be pursued regularly using effective instruments. The purpose of this study is to find out the effectiveness of antenatal risk questionnaire (ANRQ) in identifying risk factors for psychological disorders for pregnant women. This study is a literature review that searches the library through google scholar and pubmed with the keyword Antenatal Risk Questionnaire to Assess Psychosocial Risk Factors on english data base and keyword detection of mental disorders of pregnant women in indonesian data base. The search results obtained 7 literature that were reviewed after passing the elimination process ranging from identification, screening of inclusion and exclusion criteria, literature feasibility and inclued according to the purpose of the study. The results of the study make it clear that (ANRQ) is effectively used to detect early psychological disorders of pregnant women and reliable in predicting as early as possible so that immediate care can be done for the improvement of maternal psychological health problems. It is expected that the application of use (ANRQ) can be done regularly in the practice of maternity care services in order to create quality maternal mental and physical health